ANALISIS KEMAMPUAN PENALARAN SISWA KELAS X SMK DALAM MENYELESAIKAN SOAL MATEMATIKA (JURNAL LEMMA, 2023)
Â Solving math problems requires reasoning, and each student's reasoning is different. This research aims to describe masculine and feminine gender students in the mathematical reasoning process when working on math problems. The subjects selected were 2 students from class X SMK Darul Ulum Kepuhdoko Tembelang Jombang who had the same ability. The instruments used are test sheets, questionnaires and interviews. This research is qualitative by using time triangulation to see the validity of the data. The data obtained is reduced after it is presented and conclusions are drawn. Based on the analysis obtained, the reasoning of masculine and feminine gender students in solving math problems can master the six indicators. It is just that on the masculine gender, the subject does not write down what is asked and the mathematical model of the final results of the question, but the subject understands and can explain reasoning during the interview process. Feminine subject reasoning is more coherent and can communicate straightforwardly and clearly.Â